SUICIDE ATTEMPT IN ELDERLY: AN OVERLOOKED COMPLICATION OF LATE-LIFE DEPRESSION - Yhan Batista; Novira Widajanti; Agustina Konginan (Current Internal Medicine Research and Practice Surabaya Journal, 2022)
Suicide attempt in the elderly is underestimated and underreported due to cultural reference. Triggering factors may be the results of stressful life events or acquired late-life depression. An elderly woman, 69-year-old, was rushed to the emergency room due to household cleaning liquid ingestion. There was a history of previous suicide attempts and severe depressive episodes before. Since there was no sign of severe intoxication, then, the patient was treated symptomatically. Comprehensive geriatric and psychiatric assessments concluded that the patient was in a depressive state. The patient was discharged with symptomatic treatment and antidepressants but two weeks later she completed the course by drowning herself in a river.